1992
DOI: 10.1017/s0021859600014180
|View full text |Cite
|
Sign up to set email alerts
|

Digestion and nitrogen conservation in cattle and buffaloes given rice straw with or without molasses

Abstract: S U M M A R YUsing [ 14 C]urea, the rates of urea synthesis in the body, excretion in the urine and degradation in the rumen and gut were compared in 20-month-old Kedah-Kelantan cattle and swamp buffaloes at the Universiti Pertanian Malaysia, Malaysia in 1987. The animals were fed rice straw or straw plus molasses.The buffaloes were heavier than the cattle and had higher straw and nitrogen intakes, although these intakes did not differ significantly when compared on the basis of metabolic liveweight (W°'").Rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1
3

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
2
2
1
3
Order By: Relevance
“…However, when intake was expressed as percent of the bodyweight or as per metabolic body size, the TDMI was not significantly different between species. This is in agreement with that reported by other workers (Abdullah et al . 1992) .…”
Section: Resultssupporting
confidence: 94%
“…However, when intake was expressed as percent of the bodyweight or as per metabolic body size, the TDMI was not significantly different between species. This is in agreement with that reported by other workers (Abdullah et al . 1992) .…”
Section: Resultssupporting
confidence: 94%
“…This may indicate that these other N sources cause N utilization in the rumen of Brahman cattle, and were either incorporated into microbial‐N or passed to the lower gut as a bypass protein. The mean BUN concentration, 16.5–39.0 mg/dL, observed in swamp buffaloes in this study was higher than the concentration of 5.1–5.7 mg/dL observed by Abdullah et al . (1992).…”
Section: Discussioncontrasting
confidence: 91%
“…Likewise, Moran (1983) in their experiment found that the buffalo had higher intake than cattle when fed elephant grass. In contrast, some workers found a similar DMI between cattle and buffalo (Abdullah et al . 1992; Lapitan et al .…”
Section: Resultsmentioning
confidence: 82%